Faith-Based Interventions in Addressing Drug and Substance abuse among the Youth Aged 13 - 35 Years in Zimbabwe: A Case of Glen Norah Islamic Community Center, Harare - Yasin Adam (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Drug and substance abuse among youth is a growing concern in Zimbabwe, particularly in urban areas like Glen Norah, Harare. Various socio-economic and psychological factors contribute to this issue, posing challenges for families, communities, and policy-makers. Objective: This study aims to explore the role of faith-based interventions in addressing drug and substance abuse among youth aged 13 to 35 within the Glen Norah Islamic Community Centre. Method: A qualitative research design was employed, using in-depth interviews, focus group discussions, and key informant interviews to collect data from affected youth, religious leaders, and community stakeholders. Result: The findings reveal multiple contributing factors to youth drug abuse, including economic deprivation, family dysfunction, peer pressure, media influence, mental health challenges, and insufficient awareness. The study presents a faith-based model that promotes multidisciplinary collaboration involving religious institutions, healthcare professionals, and community organizations. Conclusion: Faith-based approaches, when integrated with other sectors, offer promising avenues for addressing youth substance abuse. Tailoring interventions to cultural and religious contexts enhances their relevance and impact. Contribution: This study provides actionable insights for developing context-specific, faith-informed policy and intervention strategies, contributing to a holistic and culturally appropriate response to drug abuse in Zimbabwe.